Safety and efficacy of trabectedin when administered in the inpatient versus outpatient setting: Clinical considerations for outpatient administration of trabectedin. Issue 24 (10th September 2019) - Jones, Robin L.; Maki, Robert G.; Patel, Shreyaskumar R.; Wang, George; McGowan, Tracy A.; Shalaby, Waleed S.; Knoblauch, Roland E.; von Mehren, Margaret; Demetri, George D.
Abstract : Background: The results of the randomized, phase 3 ET743‐SAR‐3007 trial demonstrated that trabectedin had a significantly longer progression‐free survival (PFS) compared with dacarbazine in patients with advanced leiomyosarcoma/liposarcoma after the failure of prior chemotherapy. Patients randomized to trabectedin received a 24‐hour intravenous infusion either in an inpatient or outpatient setting. Herein, the authors reported the safety, efficacy, and patient‐reported outcomes based on first infusion site of care. Methods: Patients were randomized 2:1 to trabectedin (at a dose of 1.5 mg/m 2 ) or dacarbazine (1 g/m 2 over 20‐120 minutes) with overall survival (OS) as the primary endpoint and PFS, time to disease progression, objective response rate, duration of response, safety, and patient‐reported symptom scoring as secondary endpoints. The setting of the trabectedin infusion was based on institutional preference and categorized based on the setting of the first infusion. Results: Of the 378 patients who were treated with trabectedin, 100 (27%) and 277 (73%), respectively, first received trabectedin in the inpatient and outpatient setting. No differences were observed with regard to PFS or OS based on site of care. The median PFS was 4.1 months versus 4.2 months (hazard ratio, 0.90; P = .49) for inpatients versus outpatients, respectively, and the median OS was 14.3 months versus 13.7 months (hazard ratio, 0.89; P = .40), respectively. Grade 3/4 adverse events (classified according to the National Cancer Institute Common Terminology Criteria for Adverse Events [version 4.0]) were reported in 87 inpatients (87%) compared with 219 outpatients (79%); grade 3/4 serious adverse events were reported in 43 inpatients (43%) and 92 outpatients (33%). Extravasation occurred in 0 inpatients and 5 outpatients (2%), whereas the incidence of catheter‐related complications was similar between groups (16% vs 15%). Conclusions: Although the majority of patients who were randomized to trabectedin received outpatient therapy, the outcomes of the current study suggested equivalent safety and efficacy in either setting. Abstract : The majority of patients randomized to trabectedin in the ET743‐SAR‐3007 trial have received the drug in the outpatient setting. The results of the current analysis suggest that trabectedin has equivalent efficacy and comparable safety when administered in an inpatient or outpatient setting.